Election Campaign Oversight Strategy for 2024: Addressing Bawaslu's Complexity and Challenges - Siagian, Roy M. (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2024)
The enhancement of the Election Supervisory Body's (Bawaslu) role in election oversight heavily depends on the clarity of authority provided by legal frameworks. In the context of administrative law, authority not only grants legitimacy but also serves as a boundary to prevent abuse of power. The challenges faced by Bawaslu have become increasingly complex with the emergence of social media as a new arena prone to violations, such as black campaigns, misinformation, and hate speech. However, Bawaslu's limited authority in addressing anonymous accounts creates a gap in oversight that can undermine electoral integrity. This study highlights the need to strengthen Bawaslu's legal foundation through revisions to Law Number 7 of 2017 and the development of regulations that are relevant to technological advancements. The theoretical approach emphasizes the importance of legality, attribution, delegation, and mandate in the management of authority. Moreover, it recommends the establishment of a dedicated subunit for social media oversight, supported by advanced technology and collaboration with digital platforms. The findings show that expanding Bawaslu's authority and enhancing its technical capacity are crucial steps to ensure more effective oversight in the digital era. This strategy is expected to uphold transparency, fairness, and integrity in elections while fostering a stronger and more trustworthy democracy in Indonesia.